Causal Relationship between Gut Microbiota and Pulmonary Embolism: An Analysis Using Mendelian Randomization - CEN LILAN; QIN LING; CHEN WANLING; WEI LIHUA; TANG CAIXIA; TENG XIANG; TIAN ZHE (Polish Journal of Microbiology)
Previous research has demonstrated a connection between an unbalanced gut microbiome (GM) and lung diseases, suggesting that gut bacteria may affect lung health through the “gut-lung” axis. However, the direct connection between GM and pulmonary embolism (PE) is unclear. Mendelian randomization studies were used to investigate GM’s genetic relationship with PE. A total of 18,340 independent genewide association studies (GWAS) yielded single nucleotide polymorphisms (SNPs) linked to the GM, which were then used as instrumental variables in a multiple regression analysis (MR) to examine the effect of GM on the risk of PE within the IEU Open GWAS project, which included 2,118 PE cases and 359,076 controls. The principal analytical methodology utilized in this research was inverse variance weighting (IVW), complemented by assessments for pleiotropy and heterogeneity to confirm the results’ resilience. The findings of this study are predominantly derived from the IVW method, providing evidence for causal associations between four distinct genera of GM and the risk of PE. Specifically, our analysis suggests that Slackia (p = 0.031), Oscillospira (p = 0.038), Bacteroides (p = 0.032), and Clostridium sensu stricto 1 (p = 0.049) may be linked to a decreased likelihood of developing PE. Importantly, our analysis yielded no evidence of heterogeneity or pleiotropy. In this MR study, we have established through genetic analysis that specific GM are significantly involved in the development of PE, underscoring the connection between the gut-lung axis and suggesting avenues for future research into the impact of GM on PE.